Safety of Propofol as an Induction Agent for Urgent Endotracheal Intubation in the Medical Intensive Care Unit. (December 2015) - Koenig, Seth J.; Lakticova, Viera; Narasimhan, Mangala; Doelken, Peter; Mayo, Paul H.
Purpose: Propofol is known to provide excellent intubation conditions without the use of neuromuscular blocking agents. However, propofol has adverse effects that may limit its use in the critically ill patients, particularly in the hemodynamically unstable patient. We report on the safety and efficacy of propofol for use as an agent for urgent endotracheal intubation (UEI) in the critically ill patients. Methods: We reviewed the outcomes of 472 consecutive UEIs performed by a medical intensive care unit (ICU) team at a tertiary care hospital from November 2008 through November 2012. Outcome data were collected prospectively as part of an ongoing quality improvement project. Results: Propofol was used as the sole sedative agent in 409 (87%) of the 472 patients. In 18 (4%) of the 472 patients, other agents (midazolam, lorazepam, or etomidate) were used in addition to propofol. Of the 472, 10 (2%) intubations were performed with a sedative agent other than propofol, and 35 (7%) of the 472 intubations were performed without any sedating agent. Endotracheal tube insertion was successful in all 472 patients. Complications of UEI in those patients who received propofol were as follows: desaturation (Sao 2 < 80%) 30 (7%) of the 427, hypotension (systolic blood pressure < 70 mm Hg) 19 (4%) of the 427, difficult intubation (>2 attempts) 44 (10%) of the 427, esophageal intubation 24 (6%) of the 427, aspiration 6 (1%) of the 427, and oropharyngeal injury 4 (1%) of the 427. There were no deaths. Average dose of propofol was 99 mg (standard deviation 7.39) per person. Conclusions: Our results compare favorably with the complication rate of UEI reported in the critical care and anesthesiology literature and indicate that propofol is a useful agent for airway management in the ICU.